PENERAPAN METODE RATIONAL UNIFIED PROCESS (RUP) DALAM PEMBUATAN WEB PEMBELAJARAN ELEKTRONIK UNTUK SEKOLAH MENENGAH PERTAMA - Mochammad Akbar Marwan; Naeli Umniati; Ricky Agus Tjiptanata; Raihan Budiyarto (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2022)
The Rational Unified Process (RUP) method is a process framework in software development that can be adapted to the objectives of the development organization and software project team. Electronic learning is a learning system based on formal teaching but with the help of electronic resources. The main component of electronic learning is the use of computers and the internet. This electronic learning web for Junior High Schools was created using the CodeIgniter framework. This web has three user authorities, namely administrators, teachers, and students. Web testing with the blackbox testing method worked well. Measurement of system usability was carried out on 24 respondents using a questionnaire. The questionnaire was made based on the criteria contained in the USE Questionnaire and the assessment was based on a Likert scale. The usability measurement resulted in a value of 89.08% which means it is very feasible.